Research on Influence Factors of College Students’ MOOC Learning Engagement in the Context of Credit Transfer - Xu Fang, Mingyue Ma , Guanhu Zhao , Qiwei Yue , Yi Hu , (Design Engineering, 2020)
At present, many colleges and universities choose some MOOC courses as elective courses for students. After students complete these courses and pass the examination, they can convert them into credits required for graduation. At present, there is still a lack of empirical research on the influence factors of MOOC learning engagement at home and abroad. Relevant studies show that online learning engagement is positively correlated with learning outcomes. This paper studies the influence factors of MOOC learning engagement of college students under the background of credit transfer. This paper measures college students’ MOOC learning engagement from three aspects: behavioral engagement, emotional engagement and cognitive engagement. The study found that the college students’ MOOC learning engagement still needs to be improved, including behavioral engagement, emotional engagement and cognitive engagement. Through the structural model calculation, it is found that the two variables of MOOC learning emotional engagement and cognitive engagement are positively correlated with behavioral engagement; The three variables, that are school policy, performance expectancy and perceived ease of use were positively correlated with behavioral engagement, emotional engagement and cognitive engagement; Teachers’ teaching factors are positively correlated with performance expectancy. On the basis of the above research, this paper puts forward some countermeasures and suggestions, such as improving learning input, improving MOOC teaching, perfecting relevant policy system, and considering the influence of demographic variables.